Development of Analytical Method and its Validation in Bilayer Tablet Containing Fexofenadine Hydrochloride (Immediate Release Layer) and Montelukast Sodium (Sustained Release Layer) (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of the present study was to develop and validate the analytical method for bilayer tablets.Materials and Methods: Simultaneous estimation of fexofenadine hydrochloride (HCl) and montelukastsodium in bilayer tablets by ultraviolet spectrophotometric method. Results and Discussion: The absorptionmaxima of fexofenadine HCl and montelukast sodium were found to be 259 nm and 285 nm, respectively,using phosphate buffer pH 6.8. The method obeys Beer’s law in the concentration range of 24–84 μg/ml and2–14 μg/ml for fexofenadine HCl and montelukast sodium, respectively. Different analytical parameters such aslimit of detection, limit of quantitation, accuracy, and precision were determined as per International Council forHarmonisation guidelines Q2 (R1). Conclusion: The accuracy of the method was found to be 99.71% and 99.13%for fexofenadine HCl and montelukast sodium, respectively. There is no interference shown by the excipients ofthe formulation in the method and the method can be used for routine quality control.